International cooperation as migration management instrument - Nikiforenko, Volodymyr; Nguyen, Anh (Migration & Law, 2021)
Review article on the problems of international cooperation in the field of migration, using the example of cooperation between the State Border Service of Ukraine and the International Organisation for Migration Mission in Ukraine
Keywords: Migration; International cooperation; IOM; State Border Guard Service of Ukraine